A loose principle for Sabah folktales animated character design: Adoption of Kansei Approach - Teddy Marius Soikun (2019)
In the folktale-based animation character design domain, the word ‘appeal,’ carries substantial weight. Many designers were familiar with the principles of 'appeal' as one of the essential elements. ‘Appeal’ can be defined as anything intriguing that draws and maintains attention. “Whereas the live-action actor has charisma, the animated character has appeal” (Thomas & Johnston, 1995). Related research focused on the technicality, which made animation character design 'appeal' rarely touched. The vague understanding and subjective nature of ‘appeal’ together with low supporting literature and comprehensive information had made it difficult to achieve. Local Folktales based animation also presents poor acceptance. The research aims to investigate the factor of ‘appeal’ through popular animation character designs. The ‘appeal’ information obtained from the popular animation character design is used to provide supporting methodology and literature to the animation character design domain. The research aims to develop loose principles of design to achieve 'appeal' that provides understanding, assistance, and knowledge to design new folktale-based animation character design. The research framework adopts the Kansei Engineering (K.E) method with the addition of art and design theories to further enhance the artistic effort. By using Qualitative Content Analysis (QCA), firstly, the research utilizes QCA to select seven (7) folktales based Japanese animation specimens from hundreds of animations from 1990-2015 significant with folktales traits. Japanese animation was chosen on its popularity ground through empirical research. Thirty-Six (36) animation characters determined by using the QCA and matrix system. The research produces twenty-five (25) design elements. Sixty (60) Viewer’s Impression Words (VIW) determined through the use of formalistic and visual semiotic analysis (FVSA) through ten (10) expert’s impressions. From the FVSA analysis, a measurement tool consists of sixty (60) VIW Semantic Differential (SD) scale questionnaires were distributed 100 evaluation subjects from the researcher University. The results from the measurement activity were analyzed using multivariate analysis to understand the ‘appeal’ factor. The loose principles called Animation Character Design Appeal Principles (ACDAP) were then proposed from the measurement. ACDAP was used as a loose rule of design to create new Sabah’s folktales-based animation character by selected animators, and the new animation character designs were compared with existing Sabah’s animation characters design to justify the proposed ACDAP. The ACDAP managed to assist animators in designing new Sabah’s folktales-based animation characters. Results obtained showed improvements in the structure of 'appeal' in the new design. The method had provided a way to understand the principle of ‘appeal’ embedded in existing popular animation. It also had helped the research to devise a new loose principle to achieve ‘appeal.’ The methodology used in this research and the proposed ACDAP had been proven to provide understanding, assistance, and knowledge in the folktales-based animation character design domain. Although the size of the research might not reflect the whole animation domain, However, it laid some foundations in the process of understanding and applying 'appeal' in animation character design.